Potret Kemanusiaan Dalam Bingkai Foto Analisis Semiotika Foto "Pengungsi Rohingya" Karya Chaideer Mahyuddin - LISA ILINDIA; Amin Sihabuddin; Ahmad Harun Yahya (Tabayyun: Journal of Journalism, 2023)
This study is entitled "Portraits of Humanity in Photo Frames. Photo Semiotic Analysis of "Rohingya Refugees" by Chaideer Mahyuddin". The purpose of this research is to find out the Portrait of Humanity in a Photo Frame. Semiotic Analysis of the Photo “Rohingya Refugee” by Chaideer Mahyuddin. This study uses a qualitative descriptive approach method. Data collection techniques in this study are: observation and documentation. The analysis uses the Roland Barthes model of semiotics, namely looking for denotative, connotative and mythical meanings. The results of the research are: The meaning of denotation, provides an overview of how the Rohingya refugees live in a state of deprivation and have to live in a foreigner's environment by fleeing in appalling conditions as a result of the impact of the conflict that occurred in their country of origin. The connotative meaning is that the image captured by Chaideer Mahyuddin is not just a photo shoot for the eyes to see. The mythical meaning of the Rohingya refugees who fled due to conflict in the country they live in, Indonesia with open arms accepts them to settle down temporarily and is given a proper place.